‘Please tell me about an idea you would love to realise’ - Vibeke Sjøvoll (FORMakademisk, 2022)
Choosing to pursue one design idea usually requires leaving several others behind. As a design teacher, I have experienced this at close range making me curious about what design students choose not to do and why. In this study, I look at my students’ design ideation from the perspective of care and look at the reasons for them abandoning their design ideas. Through this perspective, I will probe the role that the notion of risk plays in students’ management or processing of ideas. The findings are based on an empirical study using students’ reflections on abandoned ideas as data. Such explorations can bring some of the regulations that students are subjected to into the foreground, thus exposing how the educational system and teachers like myself affect the students’ sense of freedom, hampering their ability to experiment with their ideas. Creating awareness about students’ abandoned ideas in new and attentive ways can play an active role in strengthening the students’ contact with and ownership of their hopes and motivations. This can make a difference in the ongoing negotiations, re-negotiations and struggles about what good design education ought to be.